Media dan Perubahan Sosial Budaya - Andries Kango (Farabi, 2015)
The media plays an important role in the process of socio-cultural change in the community. With the support of technology, media has helped to break the distance between macro-social and micro-social also between macro-cultural and micro-cultural. Media brings the themes of the public to the private sphere where it entered and affected by the condition, orientation and local customs. This paper attempts to examine how the role of the media in the process of social and cultural changes in society. It can be concluded, that the role of the media lies in the ability to embed the pictures in our heads, underlie responsiveness and public attitudes toward various social objects.